من الانعزال التام إلى الاندماج الكلي: تجربة اليهودية الإصلاحية في مواجهة الحداثة الغربية - Mohd Daud, Noor Amali (Afkar: Jurnal Akidah dan Pemikiran Islam, 2010)
Current Western civilization is basically founded on rationalist, liberal and secular paradigms, and has been influenced by a certain degree of disenchantment with religion. This has had repercussions for the analysis of social realities as well as for the articulation of religious thought, modern Jewish thought being no exception. This article attempts to explore one of the significant modern movements in Jewish thought, namely Reform Judaism. It investigates the historical circumstances of the emergence of the Reform movement in Jewish socio-religious thought. It also deals with the question how the movement succeeded in shifting the Jewish self-understanding from closed and exclusive paradigms to more open and liberal ones in Germany, in particular, and in other European countries, in general.